Perbandingan profil daya tarik interpersonal berdasarkan Instrument Attraction Questioner dengan sosiometri - Fajar Bilqis (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
Study is motivated by difficulties when interpersonal attractiveness is measured by oneself. The purpose of this study is to examine what comparisons are when measuring the interpersonal attractiveness of the Interpersonal Attraction Questioner and sociometry based on students' interpersonal attractiveness profiles. The research method is quantitative descriptive. The results showed that social dimensions and tasks of interpersonal attraction can be measured using the Interpersonal Attraction Questioner, while the physical dimensions can be measured using sociometry. Thus, the social, physical, and task appeal that was previously thought to be too relative can be measured. These findings help to evaluate the child so that the task of social development can develop properly